Proceedings of the 7th Annual Conference on Genetic and Evolutionary Computation 2005
DOI: 10.1145/1068009.1068043
|View full text |Cite
|
Sign up to set email alerts
|

Promising infeasibility and multiple offspring incorporated to differential evolution for constrained optimization

Abstract: In this paper, we incorporate a diversity mechanism to the differential evolution algorithm to solve constrained optimization problems without using a penalty function. The aim is twofold: (1) to allow infeasible solutions with a promising value of the objective function to remain in the population and also (2) to increase the probabilities of an individual to generate a better offspring while promoting collaboration of all the population to generate better solutions. These goals are achieved by allowing each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 17 publications
0
29
0
Order By: Relevance
“…¤ £ well-known benchmark problems for constrained optimization. Details of each problem can be found in [4]. A summary of their main features are presented in Table 1.…”
Section: Experiments and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…¤ £ well-known benchmark problems for constrained optimization. Details of each problem can be found in [4]. A summary of their main features are presented in Table 1.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…From previous research [4] and some observations, we found, based on the DE mutation and crossover operator, that the offspring generated using them is located near one of the three random individuals selected for reproduction (about ¢ ¡ of the time) instead of being close to its parent. See rows 9 to 17 in Figure 1 for details.…”
Section: Our Approachmentioning
confidence: 92%
See 1 more Smart Citation
“…SR is proved to be efficient and highly competitive with other methods (Yu & Gen, 2010). As a general concept of constraint handling SR have been accompanied with other evolutionary algorithms including DE (Mezura-Montes, Velázquez-Reyes, & Coello Coello, 2005) and ACO (Leguizamon & Coello Coello, 2007).…”
Section: Separation Of Objective Function and Constraintsmentioning
confidence: 99%
“…a set of solutions is randomly generated). We selected Differential Evolution [17] because of several reasons: (1) it is an EA which has provided very competitive results when compared with respect to traditional EAs such as genetic algorithms and evolution strategies in real-world problems [6], (2) it is very simple to implement [17] and (3) its parameters for the crossover and mutation operators generally do not require a careful fine-tuning [13].…”
Section: Evolutionary Optimizationmentioning
confidence: 99%